KEGIATAN JURNAL BACA PADA GERAKAN LITERASI SEKOLAH (GLS) SEBAGAI SARANA KETERAMPILAN LITERASI BACA PESERTA DIDIK DI SDN TANAH TINGGI 1 - Utami, Nadila; Yuliana, Rina; Fajrudin, Lili (STKIP Persada Khatulistiwa Sintang, 2025)
This study aims to describe the implementation of reading journal activities within the School Literacy Movement (GLS) as a means to enhance students’ reading literacy skills. The focus of the research includes the planning, implementation, and outcomes of the reading journal activities conducted in Grade V of SDN Tanah Tinggi 1, Tangerang City. The study employed a qualitative descriptive approach involving the principal, Grade V-A and Grade V-B teachers, and students as primary data sources. Data were collected through interviews, observations, and documentation. The results show that the planning process for the reading journal activities at SDN Tanah Tinggi 1 was carried out systematically through needs identification, goal setting, and teacher training. The implementation of the reading journal consisted of three main stages: pre-reading, reading, and post-reading. The findings also reveal that the application of reading journals had a positive impact on students’ literacy skills, helping to build reading habits, improve reading comprehension, and develop writing and critical thinking skills among fifth-grade students.